Myocardial injury and clinical outcome in octogenarians after non-ST-elevation myocardial infarction - Pätz, Toni; Stiermaier, Thomas; Meusel, Moritz; Reinhard, Iris; Jensch, Philipp-Johannes; Rawish, Elias; Wang, Juan; Feistritzer, Hans-Josef; Schuster, Andreas; Koschalka, Alexander; Lange, Torben; Kowallick, Johannes T.; et al. (Frontiers in Cardiovascular Medicine, 2024)
Introduction: The aim of this study was to analyze age-associated myocardial injury and clinical outcome after non-ST-elevation myocardial infarction (NSTEMI). Methods: This prospective, multicenter study consists of 440 patients with NSTEMI enrolled at 7 centers. All patients were treated with primary percutaneous coronary intervention and underwent cardiac magnetic resonance (CMR) imaging 1-10 days after study inclusion. CMR parameters of myocardial injury and clinical outcome were evaluated by creating 2 subgroups: <80 years vs. ≥80 years. The clinical endpoint was the 1-year incidence of major adverse cardiac events (MACE) consisting of death, re-infarction and new congestive heart failure. Results: Elderly patients ≥80 years accounted for 13.9% of the study population and showed a divergent cardiovascular risk profile compared to the subgroup of patients <80 years. CMR imaging did not reveal significant differences regarding infarct size, microvascular obstruction, left ventricular ejection fraction or multidimensional strain analysis between the study groups. At 1-year follow-up, MACE rate was significantly increased in patients ≥80 years compared to patients aged <80 years (19.7% vs. 9.6%; p = 0.019). In a multiple stepwise logistic regression model, the number of diseased vessels, aldosterone antagonist use and left ventricular global longitudinal strain were identified as independent predictors for MACE in all patients, while there was no independent predictive value of age regarding 1-year clinical outcome. Conclusion: This prospective, multicenter analysis shows that structural and functional myocardial damage is similar in younger and older patients with NSTEMI. Furthermore, in this heterogeneous but also clinically representative cohort with reduced sample size, age was not independently associated with 1-year clinical outcome, despite an increased event rate in patients ≥80 years.